THE SOCIO-CULTURAL SIGNIFICANCE OF VALUING LINGUISTIC POLITENESS: THEORETICAL FRAMEWORKS - Mahyuni (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana, 2008)
Abstract Politeness has been discussed from different perspectives, i.e. pragmatics, sociolinguistics, the social psychology of language, psycholinguistics, developmental psychology, and anthropology. However, most authors seem to agree that politeness is a feature of language use. It is indicated that the politeness of linguistic acts is determined by their occurrence in communicative contexts rather than by inherent properties, pushes the issue even further by noting that being ‘polite’ is attributable only to speakers’ conduct, it is the conduct itself, whether in form of language use or other behaviours, that is routinely assessed as more or less polite relative to community values and norms (Fraser, 1990, Kasper, 1997). Thus, politeness is a crucial element of interpersonal communication in all cultures. This paper evaluates theories commonly used to approach the universality and the relativity of the issue. Abstrak Politeness sebagai kajian kebahasaan telah didiskusikan dari berbagai perspektif, seperti: pragmatics, sociolinguistics, psikologi sosial bahasa, psikolinguistik, psikologi perkembangan, dan antropologi. Akan tetapi semua ahli nampaknya bersepakat bahwa issue politeness sesungguhnya fitur dari penggunaan bahasa. Hal ini ditunjukkan oleh perilaku linguistik politeness banyak ditentukan oleh konteks komunikasi itu sendiri, sehingga menjadi property inheren dalam bentuk penggunaan bahasa dan perilaku kebahasaan yang setiap saat bisa dibandingkan dengan perilaku kebahasaan yang kurang pas (sopan) berdasarkan cara pandang masyarakat pengguna bahasa tertentu (Fraser, 1990, Kasper, 1997). Dengan demikian politeness merupakan faktor krusial dalam komunikasi interpersonal setiap budaya. Tulisan ini mencoba mengevaluasi teori-teori terkait yang lazim digunakan dalam mendekati universalitas dan relativitas politeness.